Some multiplicity results to the existence of three solutions for a dirichlet boundary value problem involving the p-laplacian - Heidarkhani, Shapour; Afrouzi, Ghasem Alizadeh (Mathematical Modelling and Analysis, 2011)
In this paper we prove the existence of two intervals of positive real parameters λ for a Dirichlet boundary value problem involving the p-Laplacian which admit three weak solutions, whose norms are uniformly bounded with respect to λ belonging to one of the two intervals. Our main tool is a three critical points theorem due to G. Bonanno [A critical points theorem and nonlinear differential problems, J. Global Optim., 28:249–258, 2004].